Microbiological and microscopic analysis of the pulp of non-vital traumatized teeth with intact crowns (Journal of Applied Oral Science, 2009)
OBJECTIVE: This study evaluated the presence of microorganisms and analyzed microscopically the pulp of 20 traumatized human teeth with intact crowns and clinical diagnosis of pulp necrosis, based on the association of at least three of the clinical criteria: crown discoloration, negative response to thermal and electric pulp vitality tests, positive response to vertical and horizontal percussion, pain on palpation or mobility. MATERIAL AND METHODS: Microbiological collection was performed from the root canals to evaluate the presence of microorganisms. The pulp samples were stained with hematoxylin and eosin (H.E.) for histological evaluation of possible morphological alterations. RESULTS: Analysis of results was performed by statistical tests (linear regression test and diagnostic analysis) and subjective analysis of the sections stained with H.E. and revealed that only 15% of the sample did not exhibit microbial development. The time elapsed between dental trauma and onset of endodontic intervention ranged from 15 days to 31 months; the percussion test presented high sensitivity (80%) for detection of microorganisms in the root canal of traumatized teeth; 3 teeth (15%) did not present pulp tissue, being characterized as complete autolysis; analysis of pulp samples was performed on the other 17 cases, among which 3 (15%) exhibited partial necrosis without possibility of repair and 14 presented complete necrosis; none of the clinical criteria employed for the diagnosis of pulp necrosis in traumatized teeth was pathognomonic. CONCLUSIONS: The present results allowed the following conclusions: with regard to microbiological findings, 85% of teeth presented microorganisms in the root canal, despite the presence of an intact crown. Concerning the microscopic findings, 100% of traumatized teeth presented pulp necrosis; the pulp vitality tests based on pulp response to heat, cold and vertical percussion were the most reliable to diagnose pulp necrosis in traumatized teeth.